Aberrant expression of miR‐451a contributes to 1, 2‐dichloroethane‐induced hepatic glycerol gluconeogenesis disorder by inhibiting glycerol kinase expression in NIH Swiss mice. Issue 2 (28th September 2017) - Zeng, Ni; Jiang, Hongmei; Fan, Qiming; Wang, Ting; Rong, Weifeng; Li, Guoliang; Li, Ruobi; Xu, Dandan; Guo, Tao; Wang, Fei; Zeng, Lihai; Huang, Manqi; et al.
Abstract: The identification of aberrant microRNA (miRNA) expression during chemical‐induced hepatic dysfunction will lead to a better understanding of the substantial role of miRNAs in liver diseases. 1, 2‐Dichloroethane (1, 2‐DCE), a chlorinated organic toxicant, can lead to hepatic abnormalities in occupationally exposed populations. To explore whether aberrant miRNA expression is involved in liver abnormalities mediated by 1, 2‐DCE exposure, we examined alterations in miRNA expression patterns in the livers of NIH Swiss mice after dynamic inhalation exposure to 350 or 700 mg m –3 1, 2‐DCE for 28 days. Using a microarray chip, we discovered that only mmumiR‐451a was significantly upregulated in the liver tissue of mice exposed to 700 mg m –3 1, 2‐DCE; this finding was validated by quantitative real‐time polymerase chain reaction. In vitro study revealed that it was metabolite 2‐chloroacetic acid, not 1, 2‐DCE that resulted in the upregulation of mmu‐miR‐451a in the mouse AML12 cell line. Furthermore, our data showed that the upregulation of mmu‐miR‐451a induced by 2‐chloroacetic acid could suppress the expression of glycerol kinase and lead to the inhibition of glycerol gluconeogenesis in mouse liver tissue and AML12 cells. These observations provide evidence that hepatic mmu‐miR‐451a responds to 1, 2‐DCE exposure and might induce glucose metabolism disorders by suppressing the glycerol gluconeogenesis process. Abstract : To explore whether aberrant miRNA expression is involved in liver abnormalities mediated by 1, 2‐DCE exposure, we examined alterations in miRNA expression patterns in the livers of NIH Swiss mice after dynamic inhalation exposure to 350 or 700 mg m −3 1, 2‐DCE for 28 days. Using a microarray chip, we discovered that only mmu‐miR‐451a was significantly upregulated in the liver tissue of mice exposed to 700 mg m −3 1, 2‐DCE; this finding was validated by quantitative real‐time polymerase chain reaction. In vitro study revealed that it was metabolite 2‐chloroacetic acid, not 1, 2‐DCE that resulted in the upregulation of mmu‐miR‐451a in the mouse AML12 cell line. Furthermore, our data showed that the upregulation of mmu‐miR‐451a induced by 2‐chloroacetic acid could suppress the expression of glycerol kinase and lead to the inhibition of glycerol gluconeogenesis in mouse liver tissue and AML12 cells.